A hermeneutic of vulnerability: Redeeming Cain? - Snyman, Gerrie (Stellenbosch Theological Journal, 2016)
This article inquires about the appropriation of Cain within a critical South African whiteness. The main argument is that despite Cain’s wrongdoing and punishment, he succeeded in living a fruitful life. The idea of the appropriation of Cain is based upon ideas expressed by Katharina von Kellenbach in her book, The Mark of Cain. The article looks at the story in terms of a hermeneutic of vulnerability. It starts with the notion of the decolonial turn and its delinking programme, followed by the exploring of the issue of vulnerability as illustrated by three recent incidents in South Africa as reported by some newspapers. It then proceeds to an analysis of Cain’s story, starting with early Christian interpretations in terms of fratricide, typology and association with the Jews, followed by two brief references of liberationist readings of Cain before explaining Von Kellenbach’s utilisation of the story. Finally, the article presents a reading of Cain that more or less provide some redemption for the character before drawing consequences for reading the story from the position of critical whiteness.